The crisis in science, the editors’ fault, and the role of emerging journals - Zavascki, Alexandre Prehn (Clinical and Biomedical Research, 2015)
It has been increasingly recognized by universities, journals’ editors and, probably in a less degree, by publishers, that there is a crisis in science. This is so important that recently, the Editor-in-Chief of Lancet, Richard Horton, stated that “much of the scientific literature, perhaps half, may simply be untrue.”